Supplier Selection Using the Analytical Hierarchy Process (AHP) Approach in Ma' Ipeh MSME - Waeni, Waeni; Kartini, Nuri (Ann Publisher, 2023)
In the Analytical Hierarchy Process (AHP) method, a hierarchical structure chart is formed to be able to solve a complex and unstructured problem. Which aims to define a problem from the general to the specific. The problem hierarchy is structured to assist in a decision-making process by taking into account all decision elements involved in the system. Ma'Ipeh Micro, Small and Medium Enterprises (MSME) are one of the community industries that are engaged in onion processing, in order to be able to produce a product that is in accordance with the wishes of consumers. Until now, Ma'Ipeh MSME continue to maintain performance both in terms of products and suppliers. To keep things in good condition and continue to grow, it is necessary to select suppliers that are in accordance with the needs and criteria of MSME. The purpose of this study was to find criteria for selecting suppliers, determining the priority of onion suppliers, and determining follow-up on all other onion suppliers according to their performance. The method used in this research is the AHP. The AHP method is used for effective decision making on complex issues. The criteria used in selecting suppliers include price, quality, service and quantity determination. The results of calculations using AHP, obtained the onion supplier with the best value, namely supplier Saniyah with a weight of 0.951. The next priority supplier is Karim with a weight of 0.337, then Amelia with a weight of 0.279.